the young collector's illustrated classics : the adventures of tom sawyer - Twain, Mark; Mark Twain (Division of kids book, Inc., 1996)
The Adventures of Tom Sawyer by Mark Twain is an 1876 novel following a mischievous, imaginative boy growing up along the Mississippi River. Tom, living with Aunt Polly, tricks friends into whitewashing a fence, romances Becky Thatcher, and runs away to play pirate. After witnessing a murder by Injun Joe and discovering treasure with Huckleberry Finn, Tom matures into a local hero.
English